Influence Of Financial Literacy and Financial Technology On Financial Management among Accounting Student in East Java - Pramesti, Anisa Frieda Hadi; Akbar, Fajar Syaiful (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze the influence of financial literacy and financial technology on students’ financial management behavior in the context of increasing fintech adoption among young people. Methodology: This research employs a quantitative approach using Partial Least Squares (PLS) as the data analysis technique. Data were collected through structured questionnaires distributed to active accounting students of Universitas Pembangunan Nasional “Veteran” Jawa Timur. Results: The results indicate that both financial literacy and financial technology have a positive and significant effect on students’ financial management. Students with higher financial knowledge and effective use of digital financial services tend to demonstrate more responsible and planned financial behavior. Novelty: This study integrates financial literacy and financial technology variables in explaining students’ financial management behavior within a higher education setting. Findings: Financial technology enhances financial management outcomes when accompanied by adequate financial literacy, reducing the risk of impulsive financial behavior. Originality: The originality of this study lies in its empirical evidence from accounting students, highlighting the complementary role of fintech and financial literacy in digital financial behavior. Conclusions: Strengthening financial literacy alongside responsible fintech utilization is essential to improve students’ financial management capabilities. Type of Paper: Empirical Research Paper.